The circumferential resection margins status: A comparison of robotic, laparoscopic and open total mesorectal excision for mid and low rectal cancer. Issue 6 (June 2016) - de Jesus, J.P.; Valadão, M.; de Castro Araujo, R.O.; Cesar, D.; Linhares, E.; Iglesias, A.C.
Abstract: Introduction: Minimally invasive surgery for rectal cancer (RC) is now widely performed via the laparoscopic approach, but robotic-assisted surgery may overcome some limitations of laparoscopy in RC treatment. We compared the rate of positive circumferential margins between robotic, laparoscopic and open total mesorectal excision (TME) for RC in our institution. Methods: Mid and low rectal adenocarcinoma patients consecutively submitted to robotic surgery were compared to laparoscopic and open approach. From our prospective database, 59 patients underwent robotic-assisted rectal surgery from 2012 to 2015 (RTME group) were compared to our historical control group comprising 200 open TME (OTME group) and 41 laparoscopic TME (LTME group) approaches from July 2008 to February 2012. Primary endpoint was to compare the rate of involved circumferential resection margins (CRM) and the mean CRM between the three groups. Secondary endpoint was to compare the mean number of resected lymph nodes between the three groups. Results: CRM involvement was demonstrated in 20 patients (15.5%) in OTME, 4 (16%) in LTME and 9 (16.4%) in the RTME ( p  = 0.988). The mean CRM in OTME, LTME and RTME were respectively 0.6 cm (0–2.7), 0.7 cm (0–2.0) and 0.6 cm (0–2.0) ( p  = 0.960). Overall mean LN harvest was 14 (0–56); 16 (0–52) in OTME, 13 (1–56) in LTME and 10 (0–45) in RTME ( p  = 0.156). Conclusion: Our results suggest that robotic TME has the same oncological short-term results when compared to the open and laparoscopic technique, and it could be safely offered for the treatment of mid and low rectal cancer.